PENGARUH MANAJEMEN WAKTU TERHADAP PRESTASI BELAJAR MAHASISWA PENDIDIKAN EKONOMI STAMBUK 2018 UNIMED (Magister Manajemen Universitas Wisnuwardhana, 2022)
This studi aims to determine the effect of time management on student achievment in economics Education at the State University f Medan. The type of research is quantiative research using IBM SPSS version 22. Data collection techniques are through questionnaries, observation and documentation. The result of the study show that there is a positive and significant effect of time manjement on learning achievment with t acount of 5,264 which is greater than t table of 1,990.